2013
DOI: 10.1037/prj0000028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wellness Recovery Action Planning on service utilization and need in a randomized controlled trial.

Abstract: Training in mental illness self-management reduced the self-reported need for and use of formal mental health services over time. This confirms the importance of WRAP in an era of dwindling behavioral health service availability and access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…WRAP's efficacy (25)(26)(27)(28)(29)(30)(31)(32)(33)(34) is supported by numerous nonexperimental studies (25,26,31,33), one quasi-experimental study (32), and two RCTs (27)(28)(29)(30). Both RCTs recruited relatively large samples (519 and 143 participants) with good retention rates, utilized blind assessors to administer standardized instruments of recovery outcomes, and delivered the intervention comparably to similar populations.…”
Section: Empirical Evidencementioning
confidence: 95%
See 1 more Smart Citation
“…WRAP's efficacy (25)(26)(27)(28)(29)(30)(31)(32)(33)(34) is supported by numerous nonexperimental studies (25,26,31,33), one quasi-experimental study (32), and two RCTs (27)(28)(29)(30). Both RCTs recruited relatively large samples (519 and 143 participants) with good retention rates, utilized blind assessors to administer standardized instruments of recovery outcomes, and delivered the intervention comparably to similar populations.…”
Section: Empirical Evidencementioning
confidence: 95%
“…Although the use of blind assessors reduces the potential for bias, the creator of WRAP was a coauthor in articles reporting results of both RCTs, an indicator of decreased evidential strength (18). Furthermore, the RCT that included an active control group of nutrition education revealed improvements in both conditions but no statistically significant differences between groups in symptom severity and perceived recovery (30). The remaining RCT demonstrated relatively modest changes in outcomes (28,29).…”
Section: Empirical Evidencementioning
confidence: 95%
“…Results of the recent REFOCUS trial suggested that delivering training based on the CHIME model to promote recovery-oriented practice in services may have a relatively limited impact on measures of personal recovery (13). On the other hand, positive outcomes for measures of recovery have been found for a number of self-management programs, which include materials on recovery (1416). Notably, these programs tend to incorporate a strong perspective of learning from shared lived experience, with trialed interventions typically featuring peer co-facilitation and group format delivery, encouraging peer contact and peer-to-peer discussion.…”
Section: Introductionmentioning
confidence: 99%
“…The approach is person-centered, values-based and is also increasingly reflected in the broader domain of chronic care research and practice [27]. Recovery-oriented interventions recommended in the 2014 NICE guidelines for psychosis as described by van der Krieke et al [28] include Individual Wellness Recovery Action Planning (WRAP) [29], Illness management and recovery (IMR) [30] and Individual Placement Support (IPS) [31]. However, the complex, multiple and interacting components of such interventions are challenging to implement [3235], especially compared with pharmacological interventions, despite the latter’s higher risk of adverse events [28].…”
Section: Introductionmentioning
confidence: 99%